Job Standard Parameters from Online Job Vacancy - Putro, Herlambang Haryo; Rakhmawati, Nur Rakhmawati (IPTEK Journal of Proceedings Series, 2020)
The internet has provided an efficient and economical way to provide job vacancy information to applicants in a way that is far more dynamic and consistent than happened in the past. This is directly proportional to the number of companies exploiting online technology (job portals, company websites, etc.) to make job advertisements reach a growing audience. To further optimize the selection process concerning processing time and accuracy, researchers have begun developing a sophisticated search engine to automatically sort resumes based on job offer requirements. Overcoming this problem requires the Information Extraction (IE) process. Research on IE regarding vacancies actually already exists and has been applied. Research on IE regarding vacancies actually already exists and has been applied In addition, we want to develop previous research involving all job vacancies websites to a wider extent. We realize that this limitation makes the extraction process difficult. we try to define job problems more easily, such as identifying various JSPs on job vacancy websites in Indonesia as a first step in the extraction process. Our findings in the survey of 14 job vacancy websites are 26 job standard parameters including structure collection and extraction methods. This study provides a detailed description of each component of information extraction on the job vacancy website in Indonesia. Starting from identifying the type of Structured Extraction to the output of extraction. This study also developed JSP from previous research.